Damage of the great vessels - principles of medical care - A. V. Kazantsev; E. A. Korymasov; E. P. Krivoshchekov; D. L. Pribytkov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
Modern aspects of etiology, pathogenesis, clinic, diagnosis and surgical treatment of vascular injuries of the extremities are considered. The surgical tactics in acute vascular injury are covered in detail in practical terms.